Generalized Yamabe Solitons on Hypersurfaces in Pseudo–Euclidean Spaces - Demirci, Burcu Bektaş; Fujii, Shunya; Maeta, Shun (Springer, 2024)
In this paper, we obtain a classification theorem for generalized Yamabe solitons, called conformal solitons, on pseudo–Riemannian hypersurfaces in pseudo–Euclidean spaces by taking the vector field as the tangential part of the position vector field. By using the theorem, we also obtain complete classification of Yamabe solitons, almost Yamabe solitons, k–Yamabe solitons and h–almost Yamabe solitons on pseudo– Riemannian hypersurfaces in pseudo–Euclidean space under the same assumption.
Keywords: Yamabe solitons; k–Yamabe solitons; Almost Yamabe solitons; Conformal solitons; Pseudo–Euclidean spaces